Small intestinal bacterial overgrowth and celiac disease: A systematic review with pooled‐data analysis. Issue 6 (12th February 2017) - Losurdo, G.; Marra, A.; Shahini, E.; Girardi, B.; Giorgio, F.; Amoruso, A.; Pisani, A.; Piscitelli, D.; Barone, M.; Principi, M.; Di Leo, A.; Ierardi, E.
Abstract: Background: A link between small intestinal bacterial overgrowth (SIBO) and celiac disease (CD) has been hypothesized. Methods: Literature search was performed in main medical databases. Methods of analysis/inclusion criteria were based on Preferred Reporting Items for Systematic reviews and Meta‐Analyses recommendations. The end‐point was to estimate, by a pooled‐data analysis, SIBO prevalence in CD. Proportions/percentages and their 95% confidence intervals (CI) were calculated by inverse variance method, whereas odd ratios (OR) and their 95% CI were estimated, where available, based on the Mantel‐Haenszel method. Data were entered into the RevMan 5.3 software. Key Results: Eleven articles fulfilled considered criteria. The pooled mean prevalence of SIBO in CD was 20% (95% CI of 10%‐30%). In comparison to asymptomatic controls, CD was associated to higher risk of SIBO, with an OR of 10.52 (95% CI 2.69‐41.21, P =.0007). Jejunal aspirate culture assessed SIBO prevalence of 11% (95% CI 3%‐19%) in CD, whereas breath tests detected a higher value (23%, 95% CI 10%‐37%). The pooled prevalence of SIBO in CD patients who were symptomatic despite a GFD was 28% (95% CI 10%‐47%), higher than in asymptomatic celiac patients (pooled prevalence of 10%, with a 95% CI of 3%‐16%), despite not statistically significant ( P =.06). When GFD‐unresponsive CD was defined only by clinical persistence of symptoms, the prevalence of SIBO was higher than in the case of villous atrophy association (31% vs 16% P =.33). Conclusions: The heterogeneity of available studies may not support a relationship SIBO‐CD. Nevertheless, SIBO could be more common in CD when symptoms do not improve after GFD. Abstract : A relationship between celiac disease (CD) and SIBO has been hypothesized. In particular, CD seemed to be a predisposing factor for SIBO. The prevalence of SIBO in CD is high, but the results are influenced by the test used to diagnose SIBO and by the response to gluten‐free diet. The high heterogeneity between studies is a limit to clarify the relationship between the two disorders. Nevertheless, our analysis suggests that SIBO could be more common in CD when symptoms do not improve after GFD, thus suggesting its detection and treatment in such cases before diagnosing a refractory CD.